Advanced abrasive-based nano-finishing processes: challenges, principles and recent applications. Issue 4 (12th March 2022) - Kumar, Manjesh; Alok, Anupam; Kumar, Vikash; Das, Manas
ABSTRACT: Surface quality is a critical factor impacting the durability and functionality of products. The conventional method of finishing causes many manufacturing defects in the final product. Conventional finishing approaches are not preferable for complex irregular surfaces due to inadequate controlling forces and machine movement constraints. There are two kinds of advanced finishing techniques: the first one uses magnetic fields, and the others do not. The first type covers magnetic abrasive finishing, magnetorheological (MR) finishing, and related methods, and the other one involves abrasive flow machining with a flexible system. For ultra-fine finishing of complex free-form products, the choice of polishing particles in these finishing methods performs an essential part. This article discusses different developments and modes of operation of instruments based on advanced abrasive-based finishing methods. The advanced abrasive-based devices studied over the last decade will be thoroughly reviewed, discussing their principles, challenges and applications. This article further emphasizes the detailed study related to MR polishing fluid and AFM media. Finally, the application prospects for these advanced finishing methods for polishing different complex free-form components made of various materials are discussed.